Cultural Migration in Lecturer Workload Reporting (BKD): Assessor Perspectives on the Adaptation of Digital Immigrant Lecturers Through the Lens of Critical Intercultural Communication - Wuysang, Julia Magdalena; Patriani, Ira; Rahmawati, Rahmawati; Pijoh, Feibe Engeline; Abas, Imelda Hermilinda (Technium Social Sciences Journal, 2025)
This study explores the digitalization of academic performance reporting systems, particularly the Beban Kerja Dosen (BKD) or Lecturer Workload Reporting in Indonesia, which introduces new institutional norms and challenges related to intercultural communication. Senior lecturers—categorized as “digital immigrants”—face considerable difficulties in adapting to these new digital platforms. While often reduced to technical issues, such adaptation processes in fact intersect with broader issues of intercultural communication, power relations, and epistemological tensions. This study investigates how digital immigrant lecturers interact with BKD assessors during the reporting process, positioning assessors as institutional agents who safeguard academic legitimacy and reproduce dominant values within higher education institutions. Drawing upon Critical Intercultural Communication Theory (Sorrells, 2016), Critical Pedagogy (Freire, 1970), Foucault’s Discourse Theory (1977), and Face-Negotiation Theory (Ting-Toomey, 2005), the research adopts a qualitative case study design. In-depth interviews were conducted with six senior BKD assessors and sixteen digital immigrant lecturers at Tanjungpura University, a state university in Indonesia. Data were analyzed using Critical Discourse Analysis (CDA) to uncover discursive dominance, power asymmetries, and adaptation strategies in the BKD reporting process. The findings reveal that BKD reporting functions as a contested site of cultural and political negotiation between lecturers and assessors. These interactions often result in the reproduction of reductive, quantitative metrics that oversimplify the complexity of academic performance. This study recommends the development of a more inclusive evaluation system, the implementation of targeted training programs for digital immigrant lecturers, and the integration of intercultural communication frameworks into the BKD reporting mechanism (Sorrells, 2016; Freire, 1970).